Contextual Factors Affecting Mental Health Services for Children with Comorbid Conditions of Learning and Intellectual Disability - Afsheen Masood، Muhammad Sulman، Shazia Aslam (JIE, 2024)
The current explorative research has been designed with the pivotal aim of divulging multidimensional perspective from diverse stake holders on the phenomenon of parental, familial and service-delivery factors likely to affect the mental health services for children with learning and intellectual disability. The investigation was laid out through qualitative research design and focus group was adopted to execute data collection.